Review and Prospect of the Study of Miniaturization in Central Asia - Keremu, Nuliya (Transactions on Social Science, Education and Humanities Research, 2023)
The development of Central Asian Miniaturization in Central Asia reflects the collision and fusion of multiple ethnic groups and civilizations, and the study of the coexistence of multiple civilizations in Central Asian Miniaturization is a major feature of the study of the Silk Road civilization, and the characteristics of Central Asian Miniaturization, and the elements of Miniaturization, to a certain extent, reflecting the historical and cultural phases of history and culture, and many scholars study Central Asian Miniaturization is always included in the study of the Persian cultural perspective, although the formation of the formation of Central Asian Miniaturization and the Persian Miniaturization has a fundamental relationship with the historical abundance of the relationship.Therefore, it has long attracted the attention of domestic and foreign academics, more than a hundred years since the emergence of fruitful research results, the content involves the characteristics of Central Asian paintings, painting styles, paintings, style elements, cultural pluralism and other issues, to explore the historical overview of the Central Asian socio-cultural, the results of these results, on the one hand, will help to understand the Central Asian paintings of the study of the interests of Central Asian paintings, on the other hand, will help to deepen Central Asian culture of the study of the paintings of fine and civilization exchanges on the Silk Road, and to promote Central Asia's art of the formation and development of the study has a positive significance.